Efficacy and Safety of Midazolam Oral Solution for Sedative Hypnosis and Anti-anxiety in Children: A Systematic Review and Meta-Analysis - Cheng, Xiao; Chen, Zhe; Zhang, Lingli; Xu, Peipei; Qin, Fang; Jiao, Xuefeng; Wang, Yiyi; Lin, Mao; Zeng, Linan; Huang, Liang; Yu, Dan (Frontiers in Pharmacology, 2020)
Background: Midazolam is recommended by the guidelines for sedation and hypnosis in children. Oral solution is a suitable dosage form for children. But there is no conclusive evidence for sedative-hypnosis and anti-anxiety by midazolam oral solution in children. Methods: Relevant studies were identified through searches of PubMed, Embase (Ovid), Cochrane Library, CINAHL, International Pharmaceuticals, four Chinese electronic databases, and relevant lists. Two reviewers independently selected trials, assessed trial quality, and extracted the data. Results: 89 RCTs comparing midazolam oral solution with placebo or blank (n =33), dexmedetomidine (n = 15), ketamine (n = 11), different midazolam doses (n = 10), midazolam injection (n = 8), chloral hydrate (n = 7), diazepam (n = 5), N2O (n = 5), triclofos (n = 4), butorphanol (n = 2), fentanyl (n = 2), hydroxyzine (n = 1), and thiopental (n = 1) were identified. Meta-analysis showed no significant difference in the success rate and duration of sedation and hypnosis between midazolam oral and injectable solution (P＞0.05). The success rate of sedation and hypnosis of midazolam was higher than that of ketamine [RR=1.32, 95% CI (1.07, 1.62), I2=0%, P<0.01]. No significant difference was found in the success rate of sedation and hypnosis, mask acceptance and parental separation between midazolam oral solution and dexmedetomidine (P＞0.05), and the result of one cohort study was consistent. The anxiety score of midazolam oral solution was higher than that of dexmedetomidine [MD=12.76, 95%CI (11.25, 14.27), P＜0.01]. The results of RCTs and prospective cohort study showed the incidence of ADR was 19.57% (189/966). Incidence of adverse reactions between (0.25, 0.5] mg/kg and (0.5, 1.0] mg/kg dose groups were similar [Pf (95% CI) =0.10(0.04, 0.24) and Pf (95% CI) =0.09(0.02, 0.39) respectively], higher than that of (0, 0.25] mg/kg dose group [Pf (95% CI) =0.01(0.00, 0.19)]. Conclusions: Available evidence suggests that midazolam oral solution is as good as midazolam injection and dexmedetomidine, and is better than ketamine. Based on efficacy and safety results, the dose of oral midazolam solution is recommended 0.5-1 mg/kg for children.